Central America : Big Data in Action for Development - World Bank (Washington, DC, 2015)
This report stemmed from a World Bank pilot activity to explore the potential of big data to address development challenges in Central American countries. As part of this activity we collected and analyzed a number of examples of leveraging big data for development. Because of the growing interest in this topic this report makes available to a broader audience those examples as well as the underlying conceptual framework to think about big data for development. To make effective use of big data, many practitioners emphasize the importance of beginning with a question instead of the data itself. A question clarifies the purpose of utilizing big data, whether it is for awareness, understanding, and/or forecasting. In addition, a question suggests the kinds of real-world behaviors or conditions that are of interest. These behaviors are encoded into data through some generating process which includes the media through which behavior is captured. Then various data sources are accessed, prepared, consolidated and analyzed. This ultimately gives rise to insights into the question of interest, which are implemented to effect changes in the relevant behaviors. Utilizing big data for any given endeavor requires a host of capabilities. Hardware and software capabilities are needed for interaction of data from a variety of sources in a way which is efficient and scalable. Human capabilities are needed not only to make sense of data but to ensure a question-centered approach, so that insights are actionable and relevant. To this end, cooperation between development experts as well as social scientists and computer scientists is extremely important.